Activation of a Carbon–Carbon Bond in Internal Alkynes: Vinylidene Rearrangement of Disubstituted Alkynes at an Ir Complex - Kuwabara, Takuya; Takamori, Shuhei; Kishi, Satoshi; Watanabe, Takahiro; Ikeda, Yousuke; Kodama, Shintaro; Minami, Yasunori; Hiyama, Tamejiro; Ishii, Youichi (Synlett, 2018)
Reactions of [Cp*Ir(PPh3)Cl2] with various internal acylalkynes in the presence of NaBArF4 resulted in the selective formation of iridacycles via vinylidene rearrangement. 13C-labeling experiments revealed that the acyl group selectively migrates to the other acetylenic carbon atom. This trend is the same as that in the vinylidene rearrangement of internal alkynes at a group 8 metal center.
Keywords: rearrangement; internal alkyne; reaction mechanism